META ANALISIS: DAMPAK PANDEMI COVID-19 TERHADAP SISTEM PEMBELAJARAN - Mahariyanti, Ermila; Prayunisa, Fena; Irwansah, Irwansah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2020)
This study aims to analyze several related journals to the impact of the online learning at covid-19 pandemic. The method of this research used literature study or meta-analysis which aims to analyze variousrelated journals to the theme raised. The results of the analysis obtained show that learning during the Covid-19 pandemic has an impact on students, teachers and parents. The impact on students' learning are motivation is still low, students feel bored due to the closure of schools that are too long and the lack of infrastructure that supports online learning. The impact on teachers are, for senior teachers, they have to learn more in using technology because they are accustomed face-to-face learning, and the learning is not optimal because the implementation of online learning is not evenly distributed for all students and learning tends to be teacher centered. The impact on parents are additional expenses used to buy internet quotas to support online learning by their children, and parents must be able to share their time with their daily activities with the time to guide their children during online learning. Lack of internet access is also a barrier to online learning.